Effect of honey feeding by thyrinteina arnobia males and females on their reproduction and longevity - Euzébio, Denise E.; Zanuncio, José C.; Pinto, Rosenilson; Wilcken, Carlos F. [UNESP]; Ramalho, Francisco S.; Lima, Eraldo (De Gruyter, 2013)
Nutrients obtained during the larval period can be sufficient for reproduction, but adult feeding may be necessary to reproductive maturity and ripening of eggs. Adult food requirements of Thyrinteina arnobia (Stoll) (Lepidoptera: Geometridae), the main defoliator of eucalyptus in Brazil, may present problems in the laboratory. The fecundity and longevity of T. arnobia adults fed on 15% honey solution were evaluated. This solution did not improve the reproductive capacity and longevity of T. arnobia females but it favors those of males, which could increase mating probability. This is important because T. arnobia males emerge sooner than females, and feeding them could increase their longevity and chances of mating various females.
Keywords: food supply; longevity; nutrition; reproduction